Combination of NEP 1–40 Treatment and Motor Training Enhances Behavioral Recovery After a Focal Cortical Infarct in Rats - Fang, Pei-chun (2010)
BACKGROUND AND PURPOSE: Although myelin-associated neurite outgrowth disinhibitors have shown promise in restoring motor function after stroke, their interactive effects with motor training have rarely been investigated. The present study examined whether a combinatorial treatment (NEP 1–40+motor rehabilitation) is more effective than either treatment alone in promoting motor recovery after focal ischemic injury. METHODS: Adult rats were assigned to one of 3 treatment groups (infarct/NEP 1–40+motor training, infarct/NEP 1–40 only, infarct/motor training only) and 2 control groups (infarct/no treatment, intact/no treatment). A focal ischemic infarct was induced by microinjecting endothelin-1 into the motor cortex. Therapeutic treatments were initiated 1 week postinfarct and included intraventricular infusion of the pharmacological agent NEP 1–40 and motor training (skilled reach task). Behavioral assessments on skilled reach, foot fault, and cylinder tests were conducted before the infarct and for 5 weeks postinfarct. RESULTS: Rats demonstrated significant forelimb impairment on skilled reach and foot fault tests after the infarct. Although all infarct groups improved over time, motor training alone and NEP 1–40 alone facilitated recovery on the skilled reach task at the end of treatment Weeks 2 and 4, respectively. However, only NEP 1–40 paired with motor training facilitated recovery after 1 week of treatment in addition to treatment at Weeks 2 and 4. Finally, only the NEP 1–40+motor training group maintained a performance level equivalent to that of the intact group over the entire period of posttreatment assessment. CONCLUSIONS: This study suggests that behavioral training interacts with the effects of the axonal growth promoter, NEP 1–40, and may accelerate behavioral recovery after focal cortical ischemia.